Sorghum grain as the only protein source in all-concentrate steer finishing ration; value of oyster shell in an all-concentrate ration - Smith, E.F.; Richardson, D.; Drake, C.L.; Brent, B.E. (Kansas Agricultural Experiment Station, 2011)
The National Research Council (publication 1137) recommends 10% protein (90% dry matter) to finish yearling steers. Sorghum grain in Kansas usually contains about 9 to 11 percent protein, although it may vary considerably depending on the variety, soil, weather and other variables (samples have ranged from 6 to 17%). Research has shown that under certain conditions, all-concentrate rations may be practical. Since low protein roughage is not used, a 10 percent protein ration can, in many cases, be formulations from sorghum grain alone.
Keywords: Beef; Sorghum grain; Finishing ration; Oyster shell